2013
DOI: 10.1111/bjd.12387
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the association between psoriasis and human leucocyte antigen-B

Abstract: A significant association was identified between psoriasis and 50 HLA-B alleles. The association varied in terms of race, and clinical type and onset age of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
(350 reference statements)
2
5
0
Order By: Relevance
“…15 A recent meta-analysis demonstrated that HLA-B*37 and HLA-B*57 were strongly associated (OR > 3.0) with psoriasis. 31 The association of GT with HLA-B*58 is described for the first time in the present study. Marks and Tait (1980) found an increase in the frequency of B15 in patients with GT.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…15 A recent meta-analysis demonstrated that HLA-B*37 and HLA-B*57 were strongly associated (OR > 3.0) with psoriasis. 31 The association of GT with HLA-B*58 is described for the first time in the present study. Marks and Tait (1980) found an increase in the frequency of B15 in patients with GT.…”
Section: Discussionsupporting
confidence: 59%
“…31 The association of GT with HLA-B*58 is described for the first time in the present study. Marks and Tait (1980) found an increase in the frequency of B15 in patients with GT.…”
supporting
confidence: 59%
“…It has been confirmed that this allele is more common in patients with slow disease progression to AIDS, including elite HIV controllers [42]. HLA-B*5701 may also have a significant effect in diseases, such as psoriasis [46,47] and drug-related liver injury (DILI) [48]. HLAB5701 is currently the only genetic variant that is routinely and extensively tested in HIV-infected patients.…”
Section: Hla-b*5701mentioning
confidence: 99%
“…HLA‐A*01:01 may act as a risk factor, participating in the pathological process of PsA in a Chinese Han population 13 . HLA‐B*38 , HLA‐B*13 , HLA‐B*37 , HLA‐B*27 , HLA‐B*17 and HLA‐Bw*16 are positively associated with PsA, while HLA‐B*12 and HLA‐Bw*35 are negatively associated with PsA in a White population 14 . As well as the HLA genes, the susceptibility non‐HLA genes are also shown as important in the pathogenesis of PsA.…”
Section: Introductionmentioning
confidence: 98%